Harnessing nematode-responsive promoters: A promising solution for plant parasitic nematodes management - Ashish Kumar Singh; Ila Joshi; Anil Kumar; Vishal Dinkar; Deshika Kohli; Ramanna Koulagi; Animesh Kumar; Pankaj; Pradeep Kumar Jain; Anil Sirohi (Plant Stress)
Plant-parasitic nematodes (PPNs) impose severe biotic stress on plants by damaging roots, disrupting nutrient and water uptake, and compromising overall plant health. These pests cause an estimated 173 billion in annual agricultural losses globally, posing a serious threat to food security and emphasizing the need for effective management strategies. Conventional approaches, such as chemical nematicides and crop rotation, face limitations including high costs, environmental concerns, and reduced efficacy against diverse nematode species, driving the search for sustainable and eco-friendly alternatives. Transgenic strategies, including RNA interference (RNAi) and toxin (''killer'') genes have shown promise in managing PPNs. However, these methods often rely on the constitutive promoters (eg: CaMV35S), which drives continuous gene expression, leading to off-target effects, metabolic burdens, and non-specific activation in plants already stressed by nematode infection. Nematode-inducible promoters have emerged as a superior alternative, offering precise, tissue-specific, and temporally controlled expression of target gene(s) exclusively in response to nematode infection. This review highlights advancements in PPN management, focusing on resistance genes and the critical role of nematode-responsive promoters. Key nematode inducible promoters of plant origin are discussed, validated through histochemical assays, cis-element analysis, and deletion studies. Their ability to drive resistance or killer gene expression specifically at infection sites offers a targeted and sustainable strategy for nematode control.